Fatigue Failure Analysis Of Bogie Frame Due To Static Load - Utomo, Ilham Satrio; Damayanti, Ajeng Tyas; Muhammad, Baihaqi Fadhilah (Journal of Railway Transportation and Technology, 2024)
This bogie design is used on trains. The purpose of simulation testing is necessary to ensure the strength and safety of the bogie frame design. Tests carried out to determine the durability of a construction are fatigue testing simulations. Fatigue failure is caused by fluctuating loads and it is necessary to simulate fatigue testing on the bogie. The method used in this research is the finite element method. The static test simulation results show that the maximum von Mises stress of 135.47 occurs at element 1675 with a safety factor of 2.4. The test simulation results on 9 loading combinations have a maximum average value of 110.16 MPa.